Characterization of Focused Seepage Through an Earthfill Dam Using Geoelectrical Methods. Issue 6 (16th December 2013) - Ikard, S. J.; Revil, A.; Schmutz, M.; Karaoulis, M.; Jardani, A.; Mooney, M.
Abstract Resistivity and self‐potential tomography can be used to investigate anomalous seepage inside heterogeneous earthen dams. The self‐potential (SP) signals provide a unique signature to groundwater flow because the source current density responsible for the SP signals is proportional to the Darcy velocity. The distribution of the SP signals is also influenced by the distribution of the resistivity; therefore, resistivity and SP need to be used in concert to elucidate groundwater flow pathways. In this study, a survey is conducted at a small earthen dam in Colorado where anomalous seepage is observed on the downstream face at the dam toe. The data reveal SP and direct current resistivity anomalies that are used to delineate three anomalous seepage zones within the dam and to estimate the source of the localized seepage discharge. The SP data are inverted in two dimensions using the resistivity distribution to determine the distribution of the Darcy velocity responsible for the observed seepage. The inverted Darcy velocity agrees with an estimation of the Darcy velocity from the hydraulic conductivity obtained from a slug test and the observed head gradient.